Infectious abortions in small domestic ruminants in the Iberian Peninsula: Optimization of sampling procedures for molecular diagnostics - Alzuguren, Oihane; Domínguez, Lara; Chacón, Gema; Benito, Alfredo A.; Mencía-Ares, Oscar (Frontiers in Veterinary Science, 2023)
Infectious abortions have a major impact on small domestic ruminant farms, i.e., sheep and goats, both in terms of profitability and health status. Therefore, rapid and sensitive diagnosis is essential to minimize losses. Currently, molecular techniques, such as qPCR, are routinely used for their diagnosis, which imply the need to manipulate all abortive material, with consequent biosafety risks. Here, we evaluate the frequency of the main abortifacient pathogens in small domestic ruminants in the Iberian Peninsula and also assess an alternative approach for the optimization of sampling for molecular diagnosis. A total of 392 clinical cases were analyzed from April 2020 to May 2021, evidencing that the main causative agents of abortion detected were Coxiella burnetii (49.0%), Chlamydia abortus (38.3%) and, to a lesser extent, Toxoplasma gondii (10.2%), Salmonella enterica (7.1%) and Campylobacter spp. (6.1%). An uneven distribution of these pathogens was observed between ruminant species, with a higher frequency (p < 0.05) of T. gondii, S. enterica and Campylobacter spp. in sheep than goat abortions, and among geographic areas, highlighting the higher frequency (p < 0.05) of T. gondii and Campylobacter spp. in the north compared to southeastern Spain. The alternative sampling method, consisting on the use of fetal tongues and placental swabs in replacement of the whole fetus and placental tissue, offered a very good agreement with the classical method for all pathogens, except for low concentrations of C. burnetii, which seems to have a doubtful role in abortion when its concentration in the abortifacient material is low. In conclusion, this study reveals a high frequency of infectious etiology in abortions of small domestic ruminants in the Iberian Peninsula and validates for the first time an alternative sampling method for molecular diagnosis that will help to provide rapid and accurate results while minimizing biosafety risks.